2013
DOI: 10.1016/j.jmii.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens meningitis: Epidemiology, prognostic factors and treatment outcomes

Abstract: S. marcescens meningitis is highly associated with neurosurgical procedures for brain solid tumors. CSF lactate concentration ≥2x ULN may predict an unfavorable outcome. Its mortality is not high and empiric treatment with parenteral third-generation cephalosporins may have a satisfactory clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
(24 reference statements)
1
17
0
1
Order By: Relevance
“…The value of CSF lactate levels for predicting the outcome of BM is still debatable. In this study, in a univariate analysis, the CSF lactate concentration in the first CSF sample did not discriminate the negative-outcome from the positive-outcome group and was not useful for predicting outcome, in agreement with previous reports 14,18,19 but in contrast to results from several other studies 9,10,11,12,13 . In the present study, the CSF lactate levels of the last sample were higher in the negative-outcome than in the positive-outcome group, corroborating the findings of a previous study 14 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The value of CSF lactate levels for predicting the outcome of BM is still debatable. In this study, in a univariate analysis, the CSF lactate concentration in the first CSF sample did not discriminate the negative-outcome from the positive-outcome group and was not useful for predicting outcome, in agreement with previous reports 14,18,19 but in contrast to results from several other studies 9,10,11,12,13 . In the present study, the CSF lactate levels of the last sample were higher in the negative-outcome than in the positive-outcome group, corroborating the findings of a previous study 14 .…”
Section: Discussionsupporting
confidence: 87%
“…Experimental animal studies have shown that elevated CSF lactate levels persisting after appropriate antibiotic treatment are associated with increased morbidity and mortality, and may facilitate prognostic prediction 8 . Several studies showed that CSF lactate levels were significantly different in clinical samples obtained from patients with a positive and a negative prognosis 9,10,11,12,13,14,15 .…”
mentioning
confidence: 99%
“…S. marcescens , as a typical opportunist and adaptable pathogen, is frequently isolated from polymicrobial infections in patients suffering from diseases such as pneumonia, meningitis, or urinary tract infections. Mixed bacterial populations include recalcitrant multiresistant Acinetobacter species, among other pathogens that can be Serratia cohabitants or contenders in the infected host ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative aerobic bacteria, such as Klebsiella pneumoniae, Serratia marcescens, Salmonella spp., and Pseudomonas aeruginosa, can occasionally be responsible for meningitis in certain patient groups, including infants and patients with head injuries or those undergoing postneurosurgical procedures or immunosuppression (31,47,48). M. tuberculosis is a common cause of chronic or subacute meningitis (49) and is associated with nonspecific symptoms and an absence of neck stiffness during early disease (50).…”
Section: Meningitismentioning
confidence: 99%